Halogen-coordinated copper-based MOF material, and preparation method and application thereof
Patent Information
- Application Number
- CN202610311865.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-03-13
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2046-03-13
AI Technical Summary
常规MOF材料主要通过物理吸附或路易斯酸碱作用与目标物结合,然而在成分复杂的水体系中吸附效果不佳
(1)本发明利用材料中Cu(I)与Ag+之间特异性的氧化还原反应实现吸附。该过程基于化学反应计量关系,具有本质上的高选择性,可有效排除水体中常见共存阳离子(如Na(I)、Zn(II)、Cu(II)、Fe(III)、Al(III)等)的干扰,实现对Ag+的高选择性捕获。
Smart Images

Figure CN122006671B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the fields of functional materials technology and water treatment, specifically to a halogen-coordinated copper-based MOF material, its preparation method, and its application. Background Technology
[0002] Silver is an important precious metal widely used in electronics, electroplating, photography, and medicine. Its production and use generate large amounts of silver-containing wastewater, leading to resource waste and environmental pollution. Therefore, the efficient recovery of silver from wastewater is of significant economic and environmental importance.
[0003] Currently, Ag recycling + Methods include precipitation, ion exchange, and electrolysis, but these methods generally suffer from poor selectivity, high energy consumption, and are prone to secondary pollution or are unsuitable for low concentrations of Ag. + Problems such as poor recovery rates exist. Adsorption methods show great potential due to their simple operation and low cost, but developing adsorbents with high selectivity, high adsorption capacity and good regeneration performance is a key challenge.
[0004] Metal-organic frameworks (MOFs) have attracted widespread attention in the field of adsorption separation due to their high specific surface area, tunable pore structure, and chemical properties. Conventional MOF materials mainly bind to target analytes through physical adsorption or Lewis acid-base interactions; however, their adsorption performance is poor in complex aqueous systems. When a large number of coexisting cations are present in the water, they can bind to the target Ag. + Competitive adsorption occurs, leading to the material's resistance to Ag. + The selective adsorption capacity and binding efficiency of Cu(I) are significantly reduced. Therefore, it is necessary to develop a method that utilizes the redox activity of Cu(I) to achieve the adsorption of Ag. + Highly selective, high-capacity capture materials are needed for Ag capture in complex water bodies. + Efficient recycling is of great significance. Summary of the Invention
[0005] This invention provides a halogen-coordinated copper-based MOF material, its preparation method, and its applications. The invention involves dissolving a divalent copper salt, a nitrogen-containing organic ligand, an alkali, and a chloride in deionized water, followed by a hydrothermal reaction, separation, washing, and drying to obtain the halogen-coordinated copper-based MOF material. This invention employs a one-step hydrothermal reaction synthesis, resulting in low-cost raw materials and a simple preparation process. The obtained halogen-coordinated copper-based MOF material exhibits Cu(I) redox activity, enabling the synthesis of Ag... + Its high adsorption and excellent selectivity make it suitable for Ag in complex water bodies. + Efficient recycling is of great significance.
[0006] To achieve the above objectives, the present invention provides the following technical solution: This invention provides a method for preparing halogen-coordinated copper-based MOF materials, comprising: dissolving divalent copper salt, nitrogen-containing organic ligand, alkali and chloride in deionized water, subjecting the mixture to a hydrothermal reaction, and then separating, washing and drying the mixture to obtain the halogen-coordinated copper-based MOF material.
[0007] Preferably, the divalent copper salt is copper chloride, copper sulfate, or copper nitrate.
[0008] Preferably, the nitrogen-containing organic ligand is isonicotinic acid, pyrazine, or 4,4'-bipyridine.
[0009] Preferably, the alkali is potassium hydroxide or sodium hydroxide.
[0010] Preferably, the chloride is potassium chloride or sodium chloride.
[0011] Preferably, the molar ratio of Cu(II) in the divalent copper salt, the nitrogen-containing organic ligand, the alkali, and the chlorine in the chloride is (0.8-1.5):(0.8-1.5):(0.8-1.5):(0.8-1.5).
[0012] Preferably, the hydrothermal reaction temperature is 160-200℃, and the hydrothermal reaction time is 20-50h.
[0013] The present invention also provides a halogen-coordinated copper-based MOF material prepared by the above preparation method, wherein the basic structural unit of the MOF material is a Cu-Cl-Cu ring structure formed by chloride ion bridging.
[0014] The halogen-coordinated copper-based MOF material provided by this invention has a rich pore structure, and the Cu(I) in the material reacts with Ag in the wastewater. + A redox reaction occurs, producing elemental silver which is fixed within the pores. Simultaneously, Cu(I) in the material is oxidized to Cu(II). This process can be represented as: MOF-Cu(I) + Ag + → MOF-Cu(II) + Ag 0 ↓.
[0015] Experimental results show that even in the presence of a large number of coexisting cations in the water (such as Na(I), Zn(II), Cu(II), Fe(III), Al(III), etc.), this material exhibits good resistance to Ag. + The recovery rate remained above 99.5%, and the recovery selectivity calculated using the partition coefficient (Kd) exceeded 3 × 10⁻⁶. 6 mL / g indicates that the halogen-coordinated copper-based MOF material provided by this invention has good Ag + It possesses high adsorption capacity and excellent selectivity, effectively avoiding interference from common coexisting ions.
[0016] This invention also provides halogen-coordinated copper-based MOF materials for adsorbing and / or recovering Ag in water. + Applications in [the context of the text].
[0017] Preferably, the halogen-coordinated copper-based MOF material utilizes Cu(I) and Ag in its framework. + Adsorption occurs through a redox reaction.
[0018] Therefore, the present invention has the following beneficial effects: (1) This invention utilizes Cu(I) and Ag in the material + Adsorption is achieved through a specific redox reaction. Based on stoichiometric chemical reactions, this process exhibits inherently high selectivity, effectively eliminating interference from common coexisting cations in water (such as Na(I), Zn(II), Cu(II), Fe(III), Al(III), etc.), thus achieving adsorption of Ag. + Highly selective capture.
[0019] (2) The material of this invention has a rich porous structure, which is not only suitable for Ag + The rapid diffusion provides a channel, and its pore space is more effective in anchoring the elemental silver (Ag) generated in the reaction. 0 This prevents spontaneous aggregation and deactivation of Ag, thereby ensuring that each Cu(I) active site is fully utilized, significantly improving Ag activity. + The recycling capacity.
[0020] (3) The material prepared by the present invention adsorbs Ag + The generated Cu(II) can be reduced to active Cu(I), restoring the material's adsorption capacity. This regeneration process does not require the use of corrosive reagents such as strong acids or alkalis, is mild, and is easy to operate, effectively reducing operating costs.
[0021] (4) The present invention adopts a one-step hydrothermal reaction synthesis, which has low raw material cost, simple preparation process, and is suitable for large-scale production. Attached Figure Description
[0022] Figure 1 This is a schematic diagram of the Cu-X-Cu ring structure in Cu2ClINA, Cu2BrINA, or Cu2IINA.
[0023] Figure 2 SEM images of Cu2FINA (a), Cu2ClINA (b), Cu2BrINA (c), and Cu2IINA (d).
[0024] Figure 3 The elemental composition of Cu2FINA (a), Cu2ClINA (b), Cu2BrINA (c), and Cu2IINA (d) obtained by SEM-EDS is shown.
[0025] Figure 4 XRD patterns and corresponding simulated XRD patterns of Cu2Clbipy, Cu2INA, Cu2FINA, Cu2ClINA, Cu2BrINA and Cu2IINA.
[0026] Figure 5 TEM images and corresponding elemental energy spectra of Cu2ClINA (a), Cu2BrINA (b), and Cu2IINA (c).
[0027] Figure 6 The Cu 2p XPS plots of Cu2ClINA (a), Cu2BrINA (b), Cu2IINA (c), Cu2INA (d) and Cu2Clbipy (e) are shown, along with the Cu(I) to Cu(II) ratio plot obtained from the Cu 2p XPS plots (f).
[0028] Figure 7 130 mg L -1 Ag + Adsorption kinetics (a) of Cu₂ClINA, Cu₂BrINA, Cu₂IINA, Cu₂INA and Cu₂Clbipy at concentrations of 50 mg L⁻¹ -1 (b) and 10 mg L -1 (c)Ag + Adsorption kinetics of Cu₂ClINA, Cu₂BrINA and Cu₂IINA at concentrations of 10 mg / L -1 Ag + The mass transfer coefficient (d) is obtained by fitting the mass transfer model.
[0029] Figure 8 500 mg L -1 Ag + Recovery capacity of Cu2ClINA, Cu2BrINA, Cu2IINA, Cu2INA and Cu2Clbipy at different concentrations.
[0030] Figure 9 Cu2ClINA in the presence of competing cations for Ag + Recovery rates of competing cations (a) and recovery selectivity coefficients calculated by Kd (b).
[0031] Figure 10 Cu2ClINA at 100 mg L -1 Ag + Cyclic adsorption performance at different concentrations (a) and Cu2ClINA before and after adsorption and after regeneration (b).
[0032] Figure 11 500 mg L -1 Ag + XRD patterns of Cu₂ClINA (a), Cu₂BrINA (b), and Cu₂IINA (c) after adsorption at certain concentrations, and the Ag content in the adsorbed products obtained by XRD refinement. 0 Molar ratio diagram (d) of AgX (X=Cl / Br / I). Detailed Implementation
[0033] The present invention will be further described below with reference to specific embodiments. Those skilled in the art will be able to implement the present invention based on these descriptions. Furthermore, the embodiments of the present invention described below are generally only some, not all, of the embodiments of the present invention. Therefore, all other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort should fall within the scope of protection of the present invention.
[0034]
Example
[0035] Example 2 This comparative example is basically the same as Example 1, except that KOH is replaced with an equimolar amount of NaOH and KCl is replaced with an equimolar amount of NaCl.
[0036] Comparative Example 1 CuF2 (2.22 mmol, 0.228 g), isonicotinic acid (2.23 mmol, 0.275 g), KOH (2.23 mmol, 0.125 g), and KF (2.24 mmol, 0.094 g) were dissolved in deionized water (15 mL). The solution was then magnetically stirred at room temperature for 1 hour. The solution was then transferred to a 50 mL polytetrafluoroethylene-lined container, sealed, and placed in a stainless steel hydrothermal reactor. The reactor was placed in an oven at 180 °C for 24 hours. Finally, the product was washed several times with deionized water and dried in a vacuum drying oven to obtain F-coordinated copper-based MOF, denoted as Cu2FINA.
[0037] Comparative Example 2 CuBr2 (2.24 mmol, 0.500 g), isonicotinic acid (2.23 mmol, 0.275 g), KOH (2.23 mmol, 0.125 g), and KBr (2.24 mmol, 0.267 g) were dissolved in deionized water (15 mL). The solution was then magnetically stirred at room temperature for 1 hour. The solution was then transferred to a 50 mL polytetrafluoroethylene-lined container, sealed, and placed in a stainless steel hydrothermal reactor. The reactor was placed in an oven at 160 °C for 48 hours. Finally, the product was washed several times with deionized water and dried in a vacuum drying oven to obtain a Br-coordinated copper-based MOF, denoted as Cu2BrINA.
[0038] Comparative Example 3 CuI (2.24 mmol, 0.427 g), isonicotinic acid (2.23 mmol, 0.275 g), KOH (2.23 mmol, 0.125 g), and KI (2.24 mmol, 0.372 g) were dissolved in deionized water (15 mL) and then magnetically stirred at room temperature for 1 hour. The solution was then transferred to a 50 mL polytetrafluoroethylene-lined container, sealed, and placed in a stainless steel hydrothermal reactor. The reactor was then placed in an oven at 140 °C for 48 hours. Finally, the product was washed several times with deionized water and dried in a vacuum drying oven to obtain I-coordinated copper-based MOF, denoted as Cu2IINA.
[0039] Comparative Example 4 Cu(NO3)2 (2.24 mmol, 0.420 g), isonicotinic acid (2.23 mmol, 0.275 g), KOH (2.23 mmol, 0.125 g), and KNO3 (2.24 mmol, 0.226 g) were dissolved in deionized water (15 mL). The solution was then magnetically stirred at room temperature for 1 hour. The solution was then transferred to a 50 mL polytetrafluoroethylene-lined container, sealed, and placed in a stainless steel hydrothermal reactor. The reactor was then placed in an oven at 140 °C for 48 hours. Finally, the product was washed several times with deionized water and dried in a vacuum drying oven to obtain a halogen-free coordinated copper-based MOF, denoted as Cu2INA.
[0040] Comparative Example 5 CuCl2 (2.23 mmol, 0.300 g), 4,4'-bipyridine (2.24 mmol, 0.350 g), KOH (2.23 mmol, 0.125 g), and KCl (2.23 mmol, 0.174 g) were dissolved in 15 mL of 50% ethanol solution. The solution was then magnetically stirred at room temperature for 1 hour. The solution was then transferred to a 50 mL polytetrafluoroethylene-lined container, sealed, and placed in a stainless steel hydrothermal reactor. The reactor was placed in an oven at 180 °C for 24 hours. Finally, the product was washed several times with ethanol and deionized water and dried in a vacuum drying oven to obtain Cl-coordinated copper-based pyridine MOF, denoted as Cu2Clbipy.
[0041] [Performance Testing] Copper-based MOF materials for Ag + Adsorption kinetics test: Add 50 mL of 10, 50, or 130 mg L to a beaker. -1 Ag + Deionized aqueous solutions were prepared by weighing 10 mg of each of the following: Cu₂ClINA / Cu₂BrINA / Cu₂IINA / Cu₂INA / Cu₂Clbipy. The solutions were then added to beakers and magnetically stirred at room temperature. Ag was measured at different reaction times. + Concentration and kinetic data were recorded. The concentration of metal ions in the solution was determined using an Agilent inductively coupled plasma mass spectrometer (ICP-OES 5800). Ag was used. + The stock solution was prepared with AgNO3.
[0042] Copper-based MOF materials for Ag + Recovery capacity test: Add 50 mL of 500 mg L to a beaker. -1 Ag + Deionized aqueous solutions were prepared by weighing 10 mg of each of the following: Cu₂ClINA / Cu₂BrINA / Cu₂IINA / Cu₂INA / Cu₂Clbipy. The solutions were then magnetically stirred at room temperature for 24 hours, and the Ag content was determined. + Concentration, calculate Ag + Recovery capacity. The concentration of metal ions in the solution was determined using an Agilent inductively coupled plasma mass spectrometer (ICP-OES 5800). Ag used... + The stock solution was prepared with AgNO3.
[0043] Cu2ClINA on Ag under the influence of coexisting cations + Recovery test: Prepare 6 vials containing 50 mL of 10 mg / L solution. -1 Ag +Add 100 mg L to each beaker containing deionized water. -1 Na(I), Zn(II), Cu(II), Al(III), Fe(III), and a mixed solution containing these five ions were weighed. 10 mg of Cu2ClINA material was added to 6 beakers respectively, and the mixtures were magnetically stirred at room temperature for 6 hours before the Ag was measured. + Calculate the concentration of Ag and the concentration of other cations. + Recovery rate and removal rate of other cations. The concentration of metal ions in the solution was determined using Agilent inductively coupled plasma mass spectrometry (ICP-OES 5800). Ag used... + The stock solution was prepared with AgNO3.
[0044] Copper-based MOF material Cu2ClINA against Ag + Cyclic performance test: Add 250 mL of 100 mg L to a beaker -1 Ag + Deionized aqueous solution: Weigh 50 mg of Cu2ClINA into a beaker, stir magnetically at room temperature for 24 hours, then separate the solid and liquid by vacuum filtration, and determine the Ag content in the liquid. + Concentration, calculate Ag + Recovery capacity. The solid was added to 30 mL of 0.1 mol / L sodium thiosulfate solution and stirred at room temperature for 2 hours to dissolve Ag and AgCl. The solid was then separated by filtration, dried in a vacuum drying oven, added to 5 mL of 2% KCl solution, and magnetically stirred at room temperature for 1 hour. The solution was then transferred to a 50 mL polytetrafluoroethylene (PTFE) liner and hydrothermally reacted in a 180°C oven for 24 hours to obtain regenerated material, which was reused in adsorption experiments. This adsorption-regeneration cycle was repeated 6 times. The concentration of metal ions in the solution was determined using an Agilent inductively coupled plasma mass spectrometer (ICP-OES 5800). The Ag used... + The stock solution was prepared with AgNO3.
[0045] A schematic diagram of the Cu-X-Cu ring structure in halogen-coordinated copper-based MOF materials is shown below. Figure 1 As shown.
[0046] SEM-EDS tests were performed on the copper-based MOF materials obtained in Example 1 and Comparative Examples 1-3, and the results are as follows: Figure 2 and Figure 3 As shown. Observation reveals that, Figure 2 This indicates that the synthesized Cu2FINA material exhibits a rod-like morphology, while Cu2ClINA, Cu2BrINA, and Cu2IINA mainly exhibit an irregular blocky structure, composed of stacked layered structures. From... Figure 3 As can be seen from this, no F element was detected in Cu2FINA, while Figure 3 b-d show that the corresponding Cl / Br / I elements can all be detected in Cu2ClINA, Cu2BrINA and Cu2IINA, indicating that due to the too high electronegativity of F and the too small atomic radius of F atom, a Cu-F-Cu ring structure cannot be formed, while Cl / Br / I have appropriate electronegativity and atomic radius, and can coordinate with Cu to form a Cu-Cl / Br / I-Cu ring structure.
[0047] XRD tests are performed on the copper-based MOF materials obtained in Example 1 and Comparative Examples 1-5, and the results are shown in Figure 4 . It can be observed that the synthesized copper-based MOF conforms to the expected structure, and no other impurity phases are found, indicating that the prepared copper-based MOF material has high phase purity.
[0048] TEM tests are performed on the copper-based MOF materials obtained in Example 1 and Comparative Examples 2-3, and the results are shown in Figure 5 . It can be observed that the elements Cu, N, O and Cl (Br / I) are uniformly distributed inside the copper-based MOF material.
[0049] XPS tests are performed on the copper-based MOF materials obtained in Example 1 and Comparative Examples 2-5, and the results are shown in Figure 6 . It can be observed that the synthesized Cu2ClINA, Cu2BrINA, Cu2IINA, Cu2INA and Cu2bipy all contain Cu(I) and Cu(II), but the ratio of the two (Cu(I) / Cu(II)) is different, showing a trend of Cu2INA<Cu2ClINA<Cu2Clbipy<Cu2BrINA<Cu2IINA, indicating that halogens can regulate the Cu(I) content in copper-based MOFs. In addition, the ratio of the two (Cu(I) / Cu(II)) in Cu2ClINA and Cu2Clbipy is also different, indicating that the type of ligand will also affect the Cu(I) content.
[0050] Adsorption kinetic tests are performed on the copper-based MOF materials obtained in Example 1 and Comparative Examples 2-5, and the results are shown in Figure 7 . It can be observed that among the five materials, Cu2ClINA has the fastest adsorption kinetics, followed by Cu2Clbipy, Cu2BrINA, Cu2IINA, and finally Cu2INA. The Mass transfer model is used to further quantify the mass transfer rate of the adsorption kinetics of the three materials Cu2ClINA, Cu2BrINA, and Cu2IINA. The fitted results show that Cu2ClINA has the largest mass transfer coefficient, which is 8.87×10 -5 m s -1 , followed by Cu2BrINA, which is 6.37×10-6 ms -1 The smallest is Cu2IINA, which is 1.68 × 10⁻⁶. -6 ms -1 .
[0051] Ag was used to test the copper-based MOF materials obtained in Example 1 and Comparative Examples 2-5. + The recycling capacity test results are as follows: Figure 8 As shown in the figure, Cu₂ClINA exhibits the highest recovery capacity, at 1153 mg / g. -1 It has a significantly higher recovery capacity than Cu2BrINA, Cu2IINA, and Cu2INA (>2 times), highlighting its performance in Ag. + It has enormous potential applications in recycling.
[0052] The copper-based MOF material obtained in Example 1 was subjected to Ag in the presence of competing cations. + Recovery rate and recovery capacity tests of competing cations, the results are as follows: Figure 9 As shown. By Figure 9 Observations show that single divalent or trivalent metal ions in the solution, including Na(I), Zn(II), Cu(II), Fe(III), and Al(III), have almost no effect on Ag. + The recovery rate. Even under conditions where all five ions coexist, Cu₂ClINA for Ag + The recovery rate remained above 99.5%, significantly higher than the removal rates of the other six coexisting ions (below 7%). Figure 9 b. Observation shows that Cu2ClINA affects Ag + The selectivity coefficient exceeds 3×10 6 The selectivity of Cu2ClINA for Ag in the presence of competing cations is 3-4 orders of magnitude higher than that of Cu2ClINA for other competing cations, indicating that Cu2ClINA is more selective for Ag in the presence of competing cations. + Excellent recycling selectivity.
[0053] The cyclic adsorption performance of the copper-based MOF material obtained in Example 1 was tested, and the results are as follows: Figure 10 As shown. By Figure 10 Observations show that after six cycles, Cu2ClINA has a lower effect on 100 mg L... -1 Ag + The recovery rate remained above 95%, while the desorption efficiency remained above 90%, indicating that Cu2ClINA has good recycling performance. Figure 10 b. Observation shows that, during the adsorption of Ag +Afterwards, the Cu(I) in Cu2ClINA decreased from 55% to 17%, and after regeneration, it recovered to 51%, indicating that Cu2ClINA can reduce Cu(I) after regeneration.
[0054] At 500 mg L -1 Ag + after adsorption, the copper-based MOF materials obtained in Example 1 and Comparative Examples 2-3 were subjected to XRD testing, and the results are shown in Figure 11 . From Figure 11 a, 11b and 11c, it can be seen that after adsorption at 500 mg L -1 Ag + concentration, all three materials contain elemental silver and the corresponding silver halide, indicating that both the deposition reaction and the redox reaction of Ag occur during the adsorption process + . Figure 11 d shows that the proportions of elemental silver and the corresponding silver halide in different materials are different. Combined with Figure 5 it can be seen that the content of Cu(I) shows a trend of Cu2ClINA<Cu2BrINA<Cu2IINA, but the generation amount of Ag 0 shows a trend of Cu2ClINA>Cu2BrINA>Cu2IINA, indicating that the generation of Ag 0 depends not only on the content of Cu(I), but also on the coordination environment of Cu(I), indicating that different halogen atom coordinations will affect the redox capacity of Cu(I). The adsorption product of Cu2ClINA has the highest proportion of elemental silver content, indicating that the redox capacity of Cu(I) in Cu2ClINA is the strongest.
Claims
1. A halogen-coordinated copper-based MOF material for adsorbing and / or recovering Ag in water + The application of [the technology] is characterized by, The preparation method of the halogen-coordinated copper-based MOF material includes: dissolving divalent copper salt, nitrogen-containing organic ligand, alkali and chloride in deionized water, performing hydrothermal reaction, separating, washing and drying to obtain the halogen-coordinated copper-based MOF material. The basic structural unit of the MOF material is a Cu-Cl-Cu ring structure formed by chloride ion bridging. The nitrogen-containing organic ligand is isonicotinic acid, pyrazine, or 4,4'-bipyridine; The chloride is potassium chloride or sodium chloride.
2. The application as described in claim 1, characterized in that, The divalent copper salt is copper chloride, copper sulfate, or copper nitrate.
3. The application as described in claim 1, characterized in that, The alkali is potassium hydroxide or sodium hydroxide.
4. The application as described in claim 1, characterized in that, Cu in the divalent copper salt 2+ The molar ratio of chlorine in nitrogen-containing organic ligands, bases and chlorides is (0.8-1.5):(0.8-1.5):(0.8-1.5):(0.8-1.5).
5. The application as described in claim 1, characterized in that, The hydrothermal reaction temperature is 160-200℃, and the hydrothermal reaction time is 20-50h.
6. The application as described in claim 1, characterized in that, The halogen-coordinated copper-based MOF material utilizes Cu in its framework + With Ag + Adsorption occurs through a redox reaction.
Citation Information
Patent Citations
Preparation method of carbon dioxide electroreduction catalyst
CN118007162A
